Membangun Jalan Tengah Di Antara Kelompok Ekstrem Sebagai Salah Satu Model Moderasi Beragama Di Indonesia - Saragih, Jon Renis (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2023)
Religious moderation relates to the middle way, harmony, and balance between religious extremes. The middle path of moderation is not mathematically middle, but harmony and balance are the best choices. In the Indonesian context, the struggle between religion and secularisation is a problem that needs to be answered. In the context of religious diversity, pluralism, and particularism are often in tension and blame each other. In the theology of religions, faith and rationalization often declare the other wrong. This article discusses moderation between these extremes with respect for their positions and deepening it as a contextual form of moderation in Indonesia. The research method used was qualitative, using library sources. This research aims to obtain a model of religious restraint in Indonesia by existing extremes. The research results show that moderation in Indonesia can be done by accommodating positive values ​​from these extremes. These results can answer the struggle regarding moderation in relations between religions and the state and in relations between religions.